Unlocking the Future: EFL Students' Insights on Artificial Intelligences for Academic Writing - Assapari, Muhammad Mugni; Hidayati, Rosyadi; Mukti, Siti Raudatul Warni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Lately, the widely used and fiercely debated ChatGPT has attracted the interest of researchers, professors, lecturers, and administrators. Additionally, English as a Foreign Language (EFL) learners require AI feedback on scientific writing to improve their writing abilities. This quantitative study investigated Indonesian EFL learners' perceptions and challenges in a university English program using ChatGPT tools. This study investigated undergraduate students' viewpoints on using AI-powered ChatGPT tools in English academic writing. It focused on the main goal, results, and feedback to improve their second language writing skills. Data were collected from (n=80) students using questionnaires and semi-structured interviews to analyze their impressions. A survey was administered to EFL undergraduates in the English Language Education Study Program at Mataram State Islamic University, Indonesia. Writing ability was assessed online using Google Forms. However, students reported the advantages and difficulties of using ChatGPT for academic writing. These results demonstrate that AI-enabled digital tools can enhance student performance in EFL, academic writing, and other disciplines. The benefits and drawbacks of artificial intelligence must be studied and evaluated, and its implications for academic writing must be developed